2018
DOI: 10.1007/s10943-018-0636-9
|View full text |Cite
|
Sign up to set email alerts
|

Religion, Culture and Meaning-Making Coping: A Study Among Cancer Patients in Malaysia

Abstract: The present study aimed to explore the use of meaning-making coping mechanisms (existential, spiritual and religious coping) among ethnic Malay cancer patients in Malaysia and to investigate the impact of culture on their choice of coping methods. Twenty-nine participants with various kinds of cancer were interviewed. Four kinds of coping resources emerged from analyses of the interview transcripts: (1) relying on transcendent power, (2) supernatural or mystical beliefs, (3) finding oneself in relationships wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 27 publications
(39 reference statements)
2
32
0
1
Order By: Relevance
“…In contrast, Islam is the dominant religion in Indonesia [ 59 ]. As individuals with different religions have been found to deploy distinct types of coping (e.g., [ 60 , 61 ]), it is possible that the present results may be confounded by the religion held by the respondents. Future studies should assess all of these potential confounding factors to scrutinize their potential influence on stress and strategy deployment when making between-country comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Islam is the dominant religion in Indonesia [ 59 ]. As individuals with different religions have been found to deploy distinct types of coping (e.g., [ 60 , 61 ]), it is possible that the present results may be confounded by the religion held by the respondents. Future studies should assess all of these potential confounding factors to scrutinize their potential influence on stress and strategy deployment when making between-country comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…In a study exploring religious cancer coping strategies in Malaysian Muslim patients, cancer acceptance could take passive (waiting for God to take control), active (surrender after having tried one's best), or collaborative (relying on one's own strength as well as God's help) forms. [ 12 ] As passive/avoidant coping has been associated with negative outcomes (e.g., loss of meaning in life),[ 24 ] a number of strategies can be adopted in our setting to further enhance this coping strategy. Muslim patients in our setting can be encouraged to view carrying out religious duties such as prayers and ablutions as an active form of “redha.”[ 18 ] Collaborative “redha” involves self-volition, and it can be helpful to give Muslim patients religiously-sensitive choice options, such as choosing less sedative pain medication, so that they can maintain their ability to perform religious prayers.…”
Section: Discussionmentioning
confidence: 99%
“…In Malaysia's multicultural setting, sociocultural factors such as partner's perception, doctor–patient dynamics, religious beliefs (e.g., fate, resurrection, reincarnation), and ethnocultural practices surrounding death and burial (e.g., death taboos) have been found to impact patient views and approaches to palliative cancer situations. [ 11 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…The first pattern of benevolent religious reappraisal refers to the notion that suffering from cancer is a lesson from God. In the other pattern, suffering is seen as educational theodicy (Dein, 1997), which means that God allows suffering to test the person, later leading her/him to a better life (Ahmadi, Hussin, Ahmadi & Taufik Mohammad, 2018a) 4.1.3 Punishing God Reappraisal Ahmadi (2006, p.106) suggested that applying punishing God reappraisal as a coping method -presumably requires a belief in a God who can determine the course of individuals' lives: a God who not only created man, but also continually controls man‗s deeds and his destiny.‖…”
Section: Educational Theodicymentioning
confidence: 99%